Antiplasmodial Activity of Lignans and Extracts from Pycnanthus angolensis - Abrantes, Marta (2015)
The dichloromethane, methanol and aqueous ethanol extracts of the stem bark of Pycnanthus angolensis were evaluated for their in vitro activity against the 3D7 Plasmodium falciparum strain. The CH2Cl2 extract was the most active showing an IC50 = 1.6 mu g/mL. From this extract, a new dibenzylbutane lignan, threo-4,4'-dihydroxy-3-methoxylignan (1) named pycnantolol, together with the known lignans (-)-dihydroguaiaretic acid (2), heliobuphthalmin (3), talaumidin (4), hinokinin (5), the labdane-type diterpene ozic acid (6), and the steroids stigmast-4-en-6 beta-ol-3-one (7), beta-sitosterol (8) and stigmasterol (9) were isolated. Their structures were established on the basis of physical and spectroscopic methods, including 2 D NMR experiments (COSY, HMQC, HMBC and NOESY). The antimalarial activity of compounds 1 - 7 was evaluated against 3D7 and Dd2 P. falciparum strains. Despite the significant activity displayed by the crude CH2Cl2 extract, the isolated compounds showed weaker antiplasmodial activity. The lowest IC50 value was obtained for talaumidin (4) (IC50 = 20.7 mu g/mL against the Dd2-chloroquine resistant P. falciparum strain).. - Science and Technology Foundation (FCT), Portugal. - The authors thank Prof. Jorge Paiva (Instituto Botanico, University of Coimbra) for identification of the plant. This work was supported by the Science and Technology Foundation (FCT), Portugal.